Analysis Of Health Service Use Of Hope Family Program Participants In Increasing The Work Effectiveness Of The Wanaraya Health Center, Kikim Barat District Lahat District - Nisma Aprini; Suwanto Suwanto; Marko Ilpiyanto (UNIVED Press, 2024)
The author conducted research with the aim of finding out how the Health Services Utilization of Participants in the Family Hope Program in the Work Area of the Wanaraya Health Center, West Kikim District, Lahat Regency. The type of research used by the author is a form of field research which is qualitative research. Data processing and analysis techniques using Data Reduction, Data Presentation and Verification and Conclusion Drawing. The results of the study explain that the Family Hope Program (PKH) is very helpful for underprivileged people in utilizing and using health facilities through the Wanaraya Health Center, West Kikim District, Lahat Regency. For people in the category of elderly, pregnant women and toddlers, they are required to check themselves regularly every month in the context of eradicating malnutrition/stunting at health service facilities, both direct health centers and posyandu-posyandu which are spread across 7 (seven) villages under the working area of the Wanaraya Health Center. Many people who use or take advantage of health services through the Family Hope Program (PKH), are more dominant in utilizing health service facilities for childbirth, while the use of other health service facilities is not dominant.